Finding focus: using external focus of attention for practicing and performing music - Williams, Susan (Leiden Universiteit Leiden, 2019)
Playing music is about doing and not knowing. A musicians art is dependent on the complex motor control that is learnt over years of practice. This research is concerned with the question: What kind of focus facilitates optimal learning and performance?According to Gabriele Wulf, external focus the focussing of attention on the intended effect of ones movements has been found to be a better way to learn complex motor control than internal focus focussing on directing the bodys movements (Wulf, 2013). The research supporting this claim, challenges the way many people are taught and the way many people practice. More knowledge on why external focus is helpful for musicians needs to be available for teachers and musicians so it can be applied in music schools and conservatoires.The aim of this research is to have a better understanding of the processes involved in the learning of motor skills for music making, and to develop and investigate tools for learning and performing music that are based on focusing on musical intention.